Improved resistor characterization methods for analog design and applications - Ravi Anirudh (2018)
Technology scaling has led to the production of more low power devices and has made the design process complicated. Analog and RF designers frequently use different types of CMOS resistors in their design for ADC, DAC, Voltage reference etc. Thus it is important that characterization of different types of CMOS resistors is done and parameters that affect the resistor are extracted to analyze the device performance. Process variations change the behavior of the devices when stressed under different conditions. Hence new techniques are required for characterization and extracting the true parameters. In this dissertation, different types of CMOS resistors are studied in depth and are characterized under different conditions on latest advanced technology nodes using optimized methods. A second order polynomial equation is used as a filtering technique for extracting the parameters during characterization. The characterization of resistor is done at -40, 25, 75, 125 and 175 degrees Celsius respectively to study the effect of temperature. High voltage is also stressed upon the resistor to study the effect of voltage on resistance. Value of voltage applied to each resistor depends on the size of the resistor. More importantly, the variations and self-heating effects that occur while characterizing the temperature and voltage coefficients of resistor are eliminated by using pulsed IV, synchronous sweep measurement and current ranging methods. The back bias effect of resistor which affects the absolute value of resistance is also studied in depth. All the measurements are done with the advanced kelvin measurement technique which measures the absolute value of body resistance and eliminates the wire resistance. This study has been done on salicided poly and diffusion resistors with N+ and P+ diffusions on advanced technology nodes.